A comparison of long-term maternal mortality associated with pathologic placental separation: Highlighting possible trends and mechanisms - Sona Jasani; Atalay Demiray; Julia Stevenson; Conrad Krawiec (PLoS ONE, 2026)
Abruption and retention, two types of abnormal placental separation, are associated with significant morbidity and mortality. Though advancements in obstetric management have improved peripartum injury, patients who experience abnormal placental separation may be at risk for long-term complications. This study evaluates long-term maternal mortality in patients with abruption or retention compared to those with normal placental separation. In our cohort of 638,911 vaginal deliveries (625,890 normal, 5,435 abruption, 7,586 retention), the mortality rate was 6.4 per 1,000 in normal deliveries, 9.8 per 1,000 in abruption, and 12.0 per 1,000 in retention. When controlling for demographic factors (age, race, social determinants of health), placental retention was associated with a 95% increased mortality risk (HR 1.95, 95% CI 1.59–2.40, p < 0.001) and placental abruption with a 59% increased risk (HR 1.59, 95% CI 1.21–2.08, p < 0.001). After excluding deaths within 42 days, the association with retention remained significant (HR 1.93, p < 0.001) while abruption lost significance (HR 1.31, p = 0.089), suggesting abruption-associated mortality may be driven by acute complications. Piecewise Cox regression confirmed these temporal patterns, with retention showing persistently elevated risk across all follow-up periods. A variety of health outcomes were associated with either abruption, retention or in both abnormal placental separation groups. More research is needed to understand the mechanisms associated with abnormal placental separation and contributors to long-term mortality.